Cell type specification and diversity in subpallial organoids - Pavon, Narciso; Sun, Yubing; Pak, ChangHui (Frontiers in Genetics, 2024)
Neural organoids have emerged as valuable tools for studying the developing brain, sparking enthusiasm and driving their adoption in disease modeling, drug screening, and investigating fetal neural development. The increasing popularity of neural organoids as models has led to a wide range of methodologies aimed at continuous improvement and refinement. Consequently, research groups often improve and reconfigure protocols to create region-specific organoids, resulting in diverse phenotypes, including variations in morphology, gene expression, and cell populations. While these improvements are exciting, routine adoptions of such modifications and protocols in the research laboratories are often challenging due to the reiterative empirical testing necessary to validate the cell types generated. To address this challenge, we systematically compare the similarities and differences that exist across published protocols that generates subpallial-specific organoids to date. In this review, we focus specifically on exploring the production of major GABAergic neuronal subtypes, especially Medium Spiny Neurons (MSNs) and Interneurons (INs), from multiple subpallial organoid protocols. Importantly, we look to evaluate the cell type diversity and the molecular pathways manipulated to generate them, thus broadening our understanding of the existing subpallial organoids as well as assessing the in vitro applicability of specific patterning factors. Lastly, we discuss the current challenges and outlook on the improved patterning of region-specific neural organoids. Given the critical roles MSN and IN dysfunction play in neurological disorders, comprehending the GABAergic neurons generated by neural organoids will undoubtedly facilitate clinical translation.